2020
DOI: 10.15407/ubj92.03.033
|View full text |Cite
|
Sign up to set email alerts
|

The fibrin B?125-135 site is involved in the lateral association of protofibrils

Abstract: Earlier we reported that during the human fibrinogen to fibrin transition a neoantigenic determinant was exposed in the Bβ119-133 fragment, where a hinge locus is situated. The fibrin-specific mAb FnI-3c and its Fab-fragment with epitope in this fragment inhibited the lateral association of protofibrils. We suggested that the epitope coincided with a site involved in this process. In this work we investigated the epitope location more precisely and defined a functional role for its exposure in the hinge locus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Mapping of the Bβ chain indicated that all structural parts of this chain can be oxidized [56]. As described previously, superhelical regions of fibrinogen also influence lateral aggregation of protofibrils [57,58]. Modifications of amino acids side chains change their spatial structure, and, thereby inhibit lateral aggregation [59,60].…”
Section: Discussionmentioning
confidence: 74%
“…Mapping of the Bβ chain indicated that all structural parts of this chain can be oxidized [56]. As described previously, superhelical regions of fibrinogen also influence lateral aggregation of protofibrils [57,58]. Modifications of amino acids side chains change their spatial structure, and, thereby inhibit lateral aggregation [59,60].…”
Section: Discussionmentioning
confidence: 74%
“…Scheme of fibrinogen molecule with some effectors (antibody, protease, peptide) targeted to the distinct parts of the molecule. Modified after: [13] I-3C antibody targeted to 122-134 residue of B-chain of fibrinogen[14]; BK134-G135 is a peptide bond that is cleaved during the formation of TSK-fragment of fibrinogen[15]; B125-135 is a synthetic peptide [16]; I-5A antibody targeted to 509-610 residue of A-chain of fibrinogen[17]; AA504-S505 -is a peptide bond that is cleaved by protease II from the culture medium of Bacillus thuringiensis[18]; AA414-610 is a peptide generated by protease from the venom of Gloydius halys halys[19]; I-3B antibody targeted to 15-53 residue of B-chain of fibrinogen[20]; BR42-A43 is a peptide bond that is cleaved by protease II from the venom of Echis multisquamatis[21]; B15-118 is a synthetic peptide[22]; II-4d antibody targeted to 86-240 residue of -chain of fibrinogen[23]; 69-77 is a synthetic peptide[7]; III-3B antibody targeted to 155-160 residue of B-chain of fibrinogen[24].…”
mentioning
confidence: 99%